Preparation method of oxygen-free copper sheet for AMB ceramic copper-clad plate

By limiting the purity and oxygen content of the oxygen-free copper ingot and adopting a multi-step preparation process, including cold medium rolling and low-temperature bright annealing, the problem of uncontrollable grain size after high-temperature welding of oxygen-free copper sheets in the prior art is solved, and the stability of grain <200μm is achieved, meeting the production needs of AMB ceramic copper clad plates.

CN119553196APending Publication Date: 2025-03-04KONFOONG MATERIALS INTERNATIONAL CO LTD

Patent Information

Application Number
CN202411742312.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

It is difficult to prepare oxygen-free copper sheets that meet the requirements of AMB ceramic copper clad plates, especially after high-temperature welding, the grain size cannot be controlled within <200 μm.

Method used

By limiting the purity of the oxygen-free copper ingot ≥4N and the oxygen content <5ppm, and using the combination process of preheating, hot rolling, ordinary annealing, milling surface treatment, rough rolling, cold medium rolling + low-temperature bright annealing, the final finish rolling is obtained to obtain oxygen-free copper sheets for AMB ceramic copper clad plates.

Benefits of technology

The stability control of the grain size of the oxygen-free copper sheet after welding at 800-950℃ is achieved, ensuring that the grain is less than 200μm and meeting the production needs of AMB ceramic copper clad plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162840330000091
    Figure BDA0005162840330000091
  • Figure BDA0005162840330000101
    Figure BDA0005162840330000101
Patent Text Reader

Abstract

The invention relates to a preparation method of an oxygen-free copper sheet for an AMB ceramic copper-clad plate, and the preparation method comprises the following steps: preparing an oxygen-free copper ingot of which the purity is greater than or equal to 4N and the oxygen content is less than 5ppm, and sequentially carrying out preheating, hot rolling, common annealing, surface milling treatment, rough rolling, cold intermediate rolling and low-temperature bright annealing combined process and finish rolling to obtain the oxygen-free copper sheet for the AMB ceramic copper-clad plate, the oxygen-free copper sheet for the AMB ceramic copper-clad plate obtained through the preparation method is good in grain stability during high-temperature welding, and meanwhile the grain size after welding is smaller than 200 micrometers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor raw material preparation, and in particular to a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad plate. Background Art

[0002] Ceramic copper clad laminate is a key basic component widely used in the field of industrial electronics. How to reliably combine the copper layer with the ceramic layer is the key to manufacturing ceramic copper clad laminate. At present, the common ceramic surface copper cladding process methods are: thin film method, thick film method, chemical plating method, laser copper cladding method, direct copper deposition method (DBC) and active metal brazing method. Active metal brazing ceramic copper clad laminate, referred to as AMB ceramic copper clad laminate, is a composite substrate made by welding ceramics such as AlN and Si3N4 with oxygen-free copper at high temperature (800-950°C) in a vacuum brazing furnace using a brazing material containing a small amount of active elements (Ti, Zr, etc.). It has the characteristics of high thermal conductivity, high electrical insulation, high mechanical strength, low expansion, etc. of ceramics, and also has the high conductivity and excellent welding performance of oxygen-free copper. It has special requirements for the oxygen-free copper sheets used for welding, with a purity of 4N (99.99wt%), an oxygen content of <5ppm, a Vickers hardness (90-110Hv), and a conductivity ≥100%IACS. In particular, it has special requirements for the grains after high-temperature welding, and the grains after welding must be <200μm.

[0003] CN116042983A discloses a method for preparing a copper plate for a ceramic copper-clad laminate, the method comprising the following steps: microalloying the copper plate raw material and casting it into a copper ingot; milling the copper ingot after hot rolling, and then rough rolling and annealing and then fine rolling to obtain a finely rolled copper plate; annealing the finely rolled copper plate, and performing multiple rolling and cycle annealing to obtain a copper plate after post-treatment. The method for preparing a copper plate for a ceramic copper-clad laminate requires microalloying the copper plate raw material, and the melt of the microalloy smelting contains 60-80ppm of calcium, 50-60ppm of magnesium and 20-30ppm of molybdenum, and the total impurity content exceeds 100ppm, that is, the purity of the copper plate raw material cannot meet the 4N requirement, so the copper plate prepared by this method is not suitable for the processing of AMB ceramic copper-clad laminates.

[0004] CN106216423A discloses a production process of a highly conductive oxygen-free copper strip for a ceramic copper-clad substrate, the production process comprising the following steps: (1) high-purity copper melting and casting; (2) upward continuous casting of copper rods; (3) continuous extrusion; (4) cold rolling; (5) annealing; (6) cold rolling; (7) straightening; (8) cleaning and passivation; (9) slitting. However, it does not disclose the grain size information after the copper strip is bonded to the ceramic substrate at high temperature, so it is impossible to determine whether the oxygen-free copper strip prepared by the method is suitable for AMB ceramic copper-clad substrates.

[0005] In summary, it is necessary to develop a new method for preparing oxygen-free copper sheets for AMB ceramic copper-clad laminates. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate, which can control the grain stability of the oxygen-free copper sheet during high-temperature welding so that the grain size after welding is less than 200 μm.

[0007] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate, the preparation method comprising the following steps:

[0009] Prepare oxygen-free copper ingots with purity ≥4N and oxygen content <5ppm, and carry out preheating, hot rolling, ordinary annealing, milling surface treatment, rough rolling, cold intermediate rolling + low-temperature bright annealing combined process, and finishing rolling in sequence to obtain oxygen-free copper sheets for AMB ceramic copper clad laminates.

[0010] In the present invention, by limiting the purity and oxygen content of the oxygen-free copper ingot and limiting the preparation method thereof, the obtained oxygen-free copper sheet for AMB ceramic copper-clad laminate has a rolled grain when directly observed under a microscope, and is in a crystalline state after AMB welding at 800-950°C, and the grain is less than 200μm. The oxygen-free copper sheet for AMB ceramic copper-clad laminate prepared by the present invention has good grain stability during high-temperature welding and a small grain size after high-temperature welding.

[0011] As a preferred technical solution of the present invention, the thickness of the oxygen-free copper ingot is 100-200 mm, for example, 100 mm, 120 mm, 140 mm, 160 mm, 180 mm or 200 mm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0012] In the present invention, by limiting the thickness of the oxygen-free copper ingot, the prepared oxygen-free copper sheet for AMB ceramic copper-clad laminate has grains in a rolled state when directly observed under a microscope, and is in a crystalline state after AMB welding at 800-950°C, and the grains are less than 200μm. When the thickness is less than 100mm, the thickness of the oxygen-free copper ingot is too small, and the total rolling deformation rate is small. The prepared oxygen-free copper sheet for AMB ceramic copper-clad laminate has grains that are easily larger after AMB welding at 800-950°C. When the thickness is greater than 200mm, the thickness of the oxygen-free copper ingot is too large, and the edge of the product is easily cracked during the rolling process.

[0013] As a preferred technical solution of the present invention, the preheating temperature is 500-800°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0014] As a preferred technical solution of the present invention, the target thickness of the hot rolling is 11-16 mm, for example, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm or 16 mm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0015] As a preferred technical solution of the present invention, the annealing temperature of the ordinary annealing is 200-600°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0016] In the common annealing process described in the present invention, the annealing time of the common annealing is 1-5h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0017] As a preferred technical solution of the present invention, the blank after ordinary annealing is subjected to a milling treatment to remove the surface oxide layer and cracked edges.

[0018] As a preferred technical solution of the present invention, the target thickness of the rough rolling is 2-5mm, for example 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm and 5mm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0019] As a preferred technical solution of the present invention, the cold rolling + low-temperature bright annealing combined process includes the following contents: the rough-rolled billet is subjected to a cold rolling, and the thickness deformation rate of the cold rolling is controlled to be 20-30%, and then a low-temperature bright annealing is performed, the annealing temperature is controlled to be 250-400°C, and the annealing time is 1-5h; this is repeated at least once.

[0020] In the present invention, by limiting the preparation method to include at least 2 cold rolling + low temperature bright annealing combined processes, the high temperature heat resistance of the oxygen-free copper sheet is improved, and the grain size is smaller after 800-950°C high temperature welding. If the preparation method does not include the cold rolling + low temperature bright annealing combined process, the grain size of the prepared copper sheet is larger after 800-950°C AMB welding, and the average grain size is greater than 200μm.

[0021] In the cold rolling + low-temperature bright annealing combined process of the present invention, the rough-rolled billet is subjected to a cold rolling, and the thickness deformation rate of the cold rolling is controlled to be 20-30%, for example, 20%, 22%, 24%, 26%, 28% or 30%, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0022] The invention limits the thickness deformation rate of each cold rolling to 20-30%, so that the oxygen-free copper sheet after cold rolling has good strength, hardness and toughness, and avoids damage to the oxygen-free copper sheet during the rolling process. When the thickness deformation rate of each cold rolling is less than 20%, multiple rolling processes are required to achieve the required thickness, thereby increasing production costs and reducing production efficiency. When the thickness deformation rate of each cold rolling is greater than 30%, cracks and other damages may be generated inside the oxygen-free copper sheet, thereby affecting the strength and toughness of the oxygen-free copper sheet.

[0023] In the cold rolling + low temperature bright annealing combined process of the present invention, the annealing temperature of the low temperature bright annealing is 250-400°C, for example, 250°C, 300°C, 350°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0024] The present invention limits the temperature of low-temperature bright annealing to 250-400°C, thereby optimizing the microstructure of the oxygen-free copper sheet and making its grain distribution more uniform, so that the oxygen-free copper sheet maintains a relatively high strength. When the temperature of low-temperature bright annealing is less than 250°C, the annealing temperature is too low and may not effectively eliminate the work hardening generated during the processing, thereby affecting the plasticity and toughness of the oxygen-free copper sheet. When the temperature of low-temperature bright annealing is greater than 400°C, the annealing temperature is too high and the grains of the oxygen-free copper sheet will grow excessively, resulting in a decrease in its strength, and also increasing production costs and energy consumption.

[0025] In the combined process of cold medium rolling + low temperature bright annealing described in the present invention, the annealing time of the low temperature bright annealing is 1-5h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0026] As a preferred technical solution of the present invention, the target thickness of the cold rolling + low temperature bright annealing combination process is 1-1.2 mm, for example, 1 mm, 1.05 mm, 1.1 mm, 1.15 mm or 1.2 mm, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0027] As a preferred technical solution of the present invention, the target thickness of the finish rolling is 0.3-0.8 mm, for example, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm or 0.8 mm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0028] As a preferred technical solution of the present invention, the method comprises the following steps:

[0029] (1) Prepare oxygen-free copper ingots with a purity of ≥4N and an oxygen content of <5ppm, with a thickness of 100-200mm;

[0030] (2) preheating the oxygen-free copper ingot at 500-800° C. and directly hot-rolling the ingot to a target thickness of 11-16 mm after it is taken out of the furnace;

[0031] (3) performing ordinary annealing on the hot-rolled billet at a temperature of 200-600° C. for a time of 1-5 h;

[0032] (4) milling the blank after ordinary annealing;

[0033] (5) The milled blank is subjected to multiple rough rolling processes to a target thickness of 2-5 mm;

[0034] (6) subjecting the rough-rolled billet to a cold intermediate rolling, and controlling the thickness deformation rate of the cold intermediate rolling to 20-30%, and then subjecting the billet to a low-temperature bright annealing, controlling the annealing temperature to 250-400° C., and the annealing time to 1-5 h; repeating this process at least once; and finally rolling the billet to a target thickness of 1-1.2 mm;

[0035] (7) The cold-rolled billet is subjected to finish rolling to a target thickness of 0.3-0.8 mm, and finally is formed by finish rolling to obtain an oxygen-free copper sheet for AMB ceramic copper-clad laminate.

[0036] Compared with the prior art, the present invention has at least the following beneficial effects:

[0037] In the present invention, by limiting the purity and oxygen content of the oxygen-free copper ingot and limiting its preparation process, the high-temperature heat resistance of the oxygen-free copper sheet is improved, the stability of the crystal grains during high-temperature welding of the oxygen-free copper sheet can be controlled, and the crystal grain size of the prepared oxygen-free copper sheet is ensured to be small after the AMB welding process at 800-950°C, with an average crystal grain size of about 180μm, thereby meeting the production requirements of the AMB ceramic copper clad laminate. DETAILED DESCRIPTION

[0038] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0039] Example 1

[0040] This embodiment provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate, the method specifically comprising the following steps:

[0041] (1) preparing an oxygen-free copper ingot with a purity of 99.99% and an oxygen content of 4 ppm, and a thickness of 140 mm;

[0042] (2) preheating the oxygen-free copper ingot at 600° C. and directly hot rolling the ingot to a target thickness of 14 mm after it is taken out of the furnace;

[0043] (3) performing ordinary annealing on the hot-rolled billet at a temperature of 400°C for 3 h;

[0044] (4) milling the blank after ordinary annealing;

[0045] (5) The milled blank is subjected to multiple rough rolling processes until the target thickness is 4 mm;

[0046] (6) subjecting the rough-rolled billet to a cold intermediate rolling, and controlling the thickness deformation rate of the cold intermediate rolling to 25%, and then subjecting the billet to a low-temperature bright annealing, controlling the annealing temperature to 300° C., and the annealing time to 3 h; repeating this process twice; and finally rolling the billet to a target thickness of 1.1 mm;

[0047] (7) The cold-rolled billet is subjected to finish rolling to a target thickness of 0.5 mm, and finally is formed by finish rolling to obtain an oxygen-free copper sheet for AMB ceramic copper-clad laminate.

[0048] Example 2

[0049] This embodiment provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate, the method specifically comprising the following steps:

[0050] (1) preparing an oxygen-free copper ingot with a purity of 99.999% and an oxygen content of 3 ppm, and a thickness of 100 mm;

[0051] (2) preheating the oxygen-free copper ingot at 800° C. and directly hot-rolling the ingot to a target thickness of 11 mm after it is taken out of the furnace;

[0052] (3) The hot-rolled billet is subjected to ordinary annealing at a temperature of 200°C and an annealing time of 5 h;

[0053] (4) milling the blank after ordinary annealing;

[0054] (5) The milled blank is subjected to multiple rough rolling processes until the target thickness is 2 mm;

[0055] (6) subjecting the rough-rolled billet to a cold intermediate rolling, and controlling the thickness deformation rate of the cold intermediate rolling to 30%, and then subjecting the billet to a low-temperature bright annealing, controlling the annealing temperature to 250° C., and the annealing time to 5 h; repeating this process 3 times; and finally rolling the billet to a target thickness of 1 mm;

[0056] (7) The cold-rolled billet is finish-rolled to a target thickness of 0.3 mm, and finally finish-rolled to obtain an oxygen-free copper sheet for AMB ceramic copper-clad laminate.

[0057] Example 3

[0058] This embodiment provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate, the method specifically comprising the following steps:

[0059] (1) preparing an oxygen-free copper ingot with a purity of 99.99% and an oxygen content of 4 ppm, and a thickness of 200 mm;

[0060] (2) preheating the oxygen-free copper ingot at 500° C. and directly hot rolling the ingot to a target thickness of 16 mm after it is taken out of the furnace;

[0061] (3) The hot-rolled billet is subjected to ordinary annealing at a temperature of 600°C and an annealing time of 1 h;

[0062] (4) milling the blank after ordinary annealing;

[0063] (5) The milled blank is subjected to multiple rough rolling passes to a target thickness of 5 mm;

[0064] (6) subjecting the rough-rolled billet to a cold intermediate rolling, and controlling the thickness deformation rate of the cold intermediate rolling to 20%, and then subjecting the billet to a low-temperature bright annealing, controlling the annealing temperature to 400° C., and the annealing time to 1 h; repeating this process 4 times; and finally rolling the billet to a target thickness of 1.2 mm;

[0065] (7) The cold-rolled billet is finish-rolled to a target thickness of 0.8 mm, and finally finish-rolled to obtain an oxygen-free copper sheet for AMB ceramic copper-clad laminate.

[0066] Example 4

[0067] This embodiment provides a method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate, which is the same as that of Embodiment 1 except that the number of repetitions of the cold rolling + low-temperature bright annealing combined process in step (6) is adjusted to 0 times.

[0068] Example 5

[0069] This embodiment provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate, which is the same as Embodiment 1 except that the thickness of the oxygen-free copper ingot is adjusted to 80 mm.

[0070] Example 6

[0071] This embodiment provides a method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate, which is the same as that of Embodiment 1 except that the thickness of the oxygen-free copper ingot is adjusted to 260 mm. Since the thickness of the oxygen-free copper ingot is too large, the edge of the oxygen-free copper ingot cracks during the rolling process, and subsequent operations cannot be performed.

[0072] Example 7

[0073] This embodiment provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate, which is the same as that of Embodiment 1 except that the annealing temperature of the low-temperature bright annealing in step (6) is adjusted to 200°C.

[0074] Example 8

[0075] This embodiment provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate, which is the same as that of Embodiment 1 except that the annealing temperature of the low-temperature bright annealing in step (6) is adjusted to 500°C.

[0076] Example 9

[0077] This embodiment provides a method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate, which is the same as that of Embodiment 1 except that the thickness deformation rate of cold rolling in step (6) is adjusted to 15%.

[0078] Example 10

[0079] This embodiment provides a method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate, which is the same as that of Embodiment 1 except that the thickness deformation rate of cold rolling in step (6) is adjusted to 40%.

[0080] Comparative Example 1

[0081] This embodiment provides a method for preparing an oxygen-free copper sheet for an AMB ceramic copper-clad laminate. The difference from Example 1 is that step (6) is not included in Comparative Example 1, and the rest is the same as Example 1.

[0082] The Vickers hardness of the oxygen-free copper sheet for AMB ceramic copper clad laminate was tested using a T402MA Vickers hardness tester, the conductivity of the oxygen-free copper sheet for AMB ceramic copper clad laminate was tested using a sigma2008B conductivity meter, and the grain size of the oxygen-free copper sheet after AMB welding was observed using an Axio Obsever 5m metallographic microscope.

[0083] According to the above test method, the Vickers hardness and electrical conductivity of the oxygen-free copper sheet for AMB ceramic copper-clad laminate and the grain size of the oxygen-free copper sheet after AMB welding are obtained, and the test results are shown in Table 1.

[0084] Table 1

[0085]

[0086]

[0087] The test results show that:

[0088] (1) It can be seen from Examples 1-3 that the method for preparing the oxygen-free copper sheet for AMB ceramic copper-clad laminate provided by the present invention can control the grain stability of the oxygen-free copper sheet during high-temperature welding. The obtained oxygen-free copper sheet has a small grain size after the AMB welding process at 800-950°C, with an average grain size of about 180 μm, which meets the production requirements of the AMB ceramic copper-clad laminate.

[0089] (2) It can be seen from Example 1 and Example 4 that in Example 1, three cold rolling + low-temperature bright annealing combined process operations were performed. Compared with Example 4, which performed one cold rolling + low-temperature bright annealing combined process operation, the Vickers hardness of the oxygen-free copper sheet in Example 1 was 98 Hv, and the grain size of the oxygen-free copper sheet after AMB welding was 174 μm; while the Vickers hardness of the oxygen-free copper sheet in Example 4 was 97 Hv, and the grain size of the oxygen-free copper sheet after AMB welding was 239 μm. This shows that the present invention improves the high-temperature heat resistance of the oxygen-free copper sheet by performing at least two cold rolling + low-temperature bright annealing treatments on the rough-rolled billet, and the grain size is smaller after high-temperature welding at 800-950°C.

[0090] (3) It can be seen from Example 1 and Example 5 that the thickness of the oxygen-free copper ingot in Example 1 is 140 mm, compared with the thickness of the oxygen-free copper ingot in Example 5 of 80 mm. The Vickers hardness of the oxygen-free copper sheet in Example 1 is 98 Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 174 μm; while the Vickers hardness of the oxygen-free copper sheet in Example 5 is 94 Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 243 μm. This shows that the present invention can make the prepared oxygen-free copper sheet crystalline after AMB welding at 800-950°C, and the grain size is less than 200 μm by controlling the thickness of the oxygen-free copper ingot to 100-200 mm.

[0091] (4) It can be seen from Example 1 and Examples 7-8 that the temperature of low-temperature bright annealing in Example 1 is 300°C. Compared with the annealing temperature of 200°C for low-temperature bright annealing in Example 7 and the annealing temperature of 500°C for low-temperature bright annealing in the embodiment, the Vickers hardness of the oxygen-free copper sheet in Example 1 is 98Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 174μm; while the Vickers hardness of the oxygen-free copper sheet in Example 7 is 126Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 168μm, and the Vickers hardness of the oxygen-free copper sheet in Example 8 is 92Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 295μm. This shows that the present invention can optimize the microstructure of the oxygen-free copper sheet by controlling the temperature of low-temperature bright annealing at 250-400°C, effectively eliminate the work hardening generated during the processing, and make the grain distribution more uniform, so that the oxygen-free copper sheet maintains a higher strength.

[0092] (5) It can be seen from Example 1 and Examples 9-10 that the thickness deformation rate of the cold rolling in Example 1 is 25%. Compared with the thickness deformation rate of the cold rolling in Example 9 of 15% and the thickness deformation rate of the cold rolling in Example 10 of 40%, the Vickers hardness of the oxygen-free copper sheet in Example 1 is 98 Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 174 μm; while the Vickers hardness of the oxygen-free copper sheet in Example 9 is 93 Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 274 μm, and the Vickers hardness of the oxygen-free copper sheet in Example 10 is 115 Hv, and the grain size of the oxygen-free copper sheet after AMB welding is 257 μm. This shows that the present invention limits the thickness deformation rate of each cold rolling to 20-30%, so that the oxygen-free copper sheet after cold rolling has good strength, hardness and toughness, and avoids damage to the oxygen-free copper sheet during the rolling process.

[0093] (6) It can be seen from Example 1 and Comparative Example 1 that Comparative Example 1 does not perform cold intermediate rolling + low temperature bright annealing treatment on the rough-rolled billet, and thus cannot improve the high temperature heat resistance of the oxygen-free copper sheet. After AMB welding at 800-950°C, the grain size is relatively large, and the average grain size is 278 μm. This indicates that the present invention improves the high temperature heat resistance of the oxygen-free copper sheet by performing at least two cold intermediate rolling + low temperature bright annealing treatments on the rough-rolled billet. After high temperature welding at 800-950°C, the grain size is relatively small, and the average grain size is <200 μm.

[0094] In summary, the present invention improves the high-temperature heat resistance of the oxygen-free copper sheet by limiting the purity and oxygen content of the oxygen-free copper ingot and limiting its preparation process, and can control the stability of the grains during high-temperature welding of the oxygen-free copper sheet, thereby ensuring that the grain size of the prepared oxygen-free copper sheet is small after the AMB welding process at 800-950°C, with an average grain size of about 180μm, thereby meeting the production requirements of AMB ceramic copper clad laminates.

[0095] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate, characterized in that: The preparation method comprises the following steps: Prepare oxygen-free copper ingots with purity ≥4N and oxygen content <5ppm, and carry out preheating, hot rolling, ordinary annealing, milling surface treatment, rough rolling, cold intermediate rolling + low-temperature bright annealing combined process, and finishing rolling in sequence to obtain oxygen-free copper sheets for AMB ceramic copper clad laminates.

2. The method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate according to claim 1, wherein: The thickness of the oxygen-free copper ingot is 100-200 mm.

3. The preparation method of oxygen-free copper sheet for AMB ceramic copper-clad laminate according to claim 1 or 2, characterized in that, The preheating temperature is 500-800°C.

4. The method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate according to any one of claims 1 to 3, wherein: The target thickness of the hot rolling is 11-16 mm.

5. The method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate according to any one of claims 1 to 4, characterized in that: The annealing temperature of the ordinary annealing is 200-600° C., and the annealing time is 1-5 hours.

6. The method for preparing the oxygen-free copper sheet for AMB ceramic copper-clad laminate according to any one of claims 1 to 5, characterized in that: The target thickness of the rough rolling is 2-5 mm.

7. The method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate according to any one of claims 1 to 6, characterized in that: The cold rolling + low temperature bright annealing combined process includes the following contents: The rough rolled billet is subjected to a cold intermediate rolling, and the thickness deformation rate of the cold intermediate rolling is controlled to be 20-30%, and then a low-temperature bright annealing is performed, and the annealing temperature is controlled to be 250-400° C. and the annealing time is 1-5 hours; and this is repeated at least once.

8. The method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate according to any one of claims 1 to 7, characterized in that: The target thickness of the combined process of cold rolling and low temperature bright annealing is 1-1.2 mm.

9. The method for preparing an oxygen-free copper sheet for AMB ceramic copper-clad laminate according to any one of claims 1 to 8, wherein: The target thickness of the finish rolling is 0.3-0.8 mm.

10. The preparation method according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: (1) Prepare oxygen-free copper ingots with a purity of ≥4N and an oxygen content of <5ppm, with a thickness of 100-200mm; (2) preheating the oxygen-free copper ingot at 500-800° C. and directly hot-rolling the ingot to a target thickness of 11-16 mm after it is taken out of the furnace; (3) performing ordinary annealing on the hot-rolled billet at a temperature of 200-600° C. for a time of 1-5 h; (4) milling the blank after ordinary annealing; (5) The milled blank is subjected to multiple rough rolling processes to a target thickness of 2-5 mm; (6) subjecting the rough-rolled billet to a cold intermediate rolling, and controlling the thickness deformation rate of the cold intermediate rolling to 20-30%, and then subjecting the billet to a low-temperature bright annealing, controlling the annealing temperature to 250-400° C., and the annealing time to 1-5 h; repeating this process at least once; and finally rolling the billet to a target thickness of 1-1.2 mm; (7) The cold-rolled billet is subjected to finish rolling to a target thickness of 0.3-0.8 mm, and finally is formed by finish rolling to obtain an oxygen-free copper sheet for AMB ceramic copper-clad laminate.

Citation Information

Patent Citations

  • Production technology of high-conductivity oxygen-free copper strip for ceramic copper-clad laminate

    CN106216423A

Cited By

  • Oxygen-free copper sheet for ceramic copper-clad plate, preparation method of oxygen-free copper sheet and ceramic copper-clad plate

    CN120967269A